Konstruksi Sosial Masyarakat Percandian dalam Pemeliharaan Kearifan Lokal - Enda, Enda (TEMALI : Jurnal Pembangunan Sosial, 2020)
This study aims to determine the social construction of the Batujaya temple complex, Karawang, West Java in maintaining local wisdom. This study uses Peter L. Berger's social construction theory, which sees society as a process that takes place in three dialectical moments at once, namely externalization, objectification, and internalization. The social construction of society has a long journey from the past to the present, and the future. So that in society a social reality is created. The method used in this research is a descriptive method, which is a type of qualitative data to describe, analyze, and reveal events that occur in the field. The data sources of this research are the village government, community leaders, temple maintenance workers, and the temple community. Data collection methods used in this study were observation, interviews, and documentation. In addition, it is also equipped with secondary data in the form of reference books, tourism profiles in the form of brochures that are relevant to the research theme to support data in the field. The results showed that in order to maintain local wisdom, the people of the baths still maintain their belief in animism and dynamism. Relations between local communities are built through a process of adaptation, interaction, and socialization. Efforts to regenerate local wisdom are carried out through integrated socialization to schools and creating a tourism-loving community.